Altered CD46-mediated T cell co-stimulation in haemodialysis patients - Brinkkötter, Paul-Thomas; Marinaki, Smaragdi; Göttmann, Uwe; Fleckenstein, Sandra Magdalena; Stump-Guthier, Carolin; Woude, Fokko J. van der; Braun, Claude; Yard, Benito A. (Clinical & experimental immunology, 2005)
While most of our understanding of immune dysfunction in dialysis patients involves alterations in CD28-CD80/86 signalling, nothing is known of CD46-mediated co-stimulation of T cells in these patients. Because C3b/C4b bind to CD46 and complement activation occurs during haemodialysis (HD), we addressed whether CD46-mediated T cell activation is altered in HD (n = 9), peritoneal dialysis (PD) (n = 10) and predialysis patients (n = 8) compared to healthy controls (HC) (n = 8). T cell surface markers, T cell proliferation and interleukin (IL)-10 production were studied in CD4(+)T cells. In addition, CD46 splice-variants and IL-10 promoter gene polymorphisms were studied by reverse transcription (RT) or amplification refractory mutation system-polymerase chain reaction (ARMS-PCR), respectively. In all uraemic patients, irrespective of the stage of renal insufficiency or dialysis modality, a significant increase in the percentage of CD25 positivity in naive CD4(+)T cells was found (64% +/- 21%versus 23% +/- 18%, P < 0.001). Lymphocytes of HD patients proliferated in greater numbers and produced more IL-10 after co-stimulation with anti-CD46 than after co-stimulation with anti-CD28. This was also found in CD4(+)T cells of PD patients, albeit to a lesser extent. In contrast, with T cells of predialysis patients and of HC, co-stimulation via CD28 was more efficient. The observed alterations in T cell proliferation and IL-10 production were associated neither with CD46 splice variants nor with IL-10 promoter gene polymorphisms. Lymphocytes of HD patients show an increased response on CD46 co-stimulation. These data suggest that ongoing complement activation in HD patients may lead to alterations in acquired immunity.
Gesehen am 27.05.2022